Anti-Diabetic Activity-Guided Studies Of Syzygium Polyanthum (Wight) Leaf Extracts And Elucidation Of Their Mechanisms Of Action - Tri, Widyawati (2015)
Anti-diabetic activity guided studies were performed on the leaves of Syzygium polyanthum, a popular traditional medicinal herb in north Sumatera, Indonesia. The anti-diabetic activity was evaluated by determining whether the extracts lowered the blood glucose levels (BGL) of normal rats (hypoglycaemic test), inhibited the rise of BGL of intraperitoneally glucose- loaded rats (glucose tolerance test) and lowered BGL of streptozotocin-induced diabetic rats. Dried powdered S. polyanthum leaves were extracted serially with petroleum ether (PEE), chloroform (CE), methanol (ME) and water (WE). In diabetic rats, single-dose administration of the extracts showed that only ME reduced BGL. However, upon repeated-dose administration for 6 days both PEE and ME reduced BGL significantly. Therefore, liquid-liquid partition was used to fractionate ME into the following fractions: chloroform (CF), ethyl acetate (EAF), n-butanol (n-BF) and water (WF). Repeated administration of CF and WF decreased BGL of diabetic rats. CF was shaken with n-hexane to yield an undissolved fraction (SF-1) and a dissolved fraction (SF-2).